Analysis of the Effect of General Allocation Funds,Agglomeration, and Human Development Index on Regional Inequality in Eastern Indonesia in 2019-2023 - I Wayan Suparta; Dhea Nerizza Aditya (International Journal of Economics, Commerce, and Management, 2025)
This study aims to analyze the impact of general allocation funds, agglomeration, and human development index on regional inequality in Eastern Indonesia during the period 2019–2023. Regional inequality remains a crucial issue in Indonesia's development agenda, especially in the eastern region, which has experienced slower growth and uneven provision of public services. This study uses panel data regression analysis with secondary data. The results indicate that general allocation funds and the human development index have a significant negative impact on regional inequality, suggesting that increased fund transfers and improvements in human development can reduce inequality. Conversely, agglomeration has a significant positive impact, suggesting that economic concentration can widen disparities between regions. These findings highlight the importance of equitable development policies and investment in human capital to reduce regional disparities.